The Effect of Audio Visual Media on Learning Achievement of 2nd Grade of Civics Education in Elementary Schools - widianto, riko; Supratno, Haris; Dwi Rochmania, Desty (IJPSE : Indonesian Journal of Primary Science Education, 2021)
The purpose of this study is to add insight into the pretest-posttest result with and without the use of audio visual media on Civics Education Learning outcomes. It is also to add insight on the influence of the use of audio visual media on Civics Education Learning outcomes in 2nd grade students of Menganto Public Elemetary School.This research is quantitative with pretest-posttest, non equivalent control group design. The sample in this study was students who were divided into two groups, namely the experimental class and the control class with 12 students each group. The results showed that there was a significant influence in the use of audio-visual media on the learning outcomes of theme 6, sub-topic 3, 1st learning, rules and regulations in the school environment material. The t-test results showed that the average pretest-posttest learning outcomes of the control class was 5.944 and the average pretest-posttest learning outcomes of the experimental class were 8.437. Based on the results of the average value, it is obtained that there is an increse of student achievement before and after using audio visual media in thematic learning.